Pembuatan Minuman Kesehatan (Healthy Drink) dari Seduhan Teh Bunga Telang Kombinasi Jeruk Kalamansi di SMAN 1 Bengkulu Tengah - Herlina; Luky Dharmayanti (Bengkulu Institute, 2024)
Butterfly pea are known by various names, in English butterfly pea flowers are known as Butterfly pea tea. The Butterfly pea (Clitoria Ternatea L) has a purple, blue and white color, indicating that the Butterfly pea contains the phytochemical anthocyanin. The anthocyanin content in butterfly pea community service functions as a source of antioxidants which function as an antidote to free radicals in the body. The aim of this is to provide education or counseling about the benefits and properties and processing of butterfly pea, one of which is as a health drink combined with kalamansi orange. Community service activities were carried out at SMA Negeri 1 Bengkulu Tengah on June 10, 2023. This activity was attended by 32 students on class XI. The method of implementing service is carried out using lecture, demonstration and discussion methods. Indicators of the level of success in implementing community service use questionnaires that are distributed to students before and after carrying out community service activities. Overall, this community service activity went very smoothly and increased students' knowledge about the benefits and properties and healthy drinks from steeping butterfly pea tea experienced a large increase when seen from the total average score before counseling by 15% to 91.88% after counseling.